2016
DOI: 10.1080/1478422x.2016.1175773
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternating current interference on cathodic protection potential and its effectiveness for corrosion protection of pipelines

Abstract: In this work, the effect of alternating current (AC) interference on cathodic protection (CP) potential on a X65 steel in a near-neutral pH bicarbonate solution was investigated, and the CP performance under AC was evaluated by weight-loss measurements. The CP potential applied on the steel cannot be maintained in the presence of AC interference. The shift of the CP potential depends on the applied CP level and AC current density. No matter if the direct current potential of the steel is shifted negatively or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Conversely at −1 V vs. SCE, AC shifts potential in the positive direction. Similar observations were reported by Kuang et al [53,54]: the DC potential of X65 steel in near-neutral pH bicarbonate solution is shifted negatively by AC at −0.85 V vs. CSE, but positively shifted by AC under the CP of −1 V vs. CSE (Figure 2). Nevertheless, differently to what can be expected, the potential variation reported is higher at smaller AC density (Figure 2b).…”
Section: Effect On DC Potential (Cathodic Protection Condition)supporting
confidence: 89%
“…Conversely at −1 V vs. SCE, AC shifts potential in the positive direction. Similar observations were reported by Kuang et al [53,54]: the DC potential of X65 steel in near-neutral pH bicarbonate solution is shifted negatively by AC at −0.85 V vs. CSE, but positively shifted by AC under the CP of −1 V vs. CSE (Figure 2). Nevertheless, differently to what can be expected, the potential variation reported is higher at smaller AC density (Figure 2b).…”
Section: Effect On DC Potential (Cathodic Protection Condition)supporting
confidence: 89%
“…The high-strength steel is very sensitive to hydrogen embrittlement (Hardie et al, 2006), and X80 steel has been widely used in oil and gas pipelines (Liang et al, 2009;Lei and Shan, 2005;Feng et al, 2020). Alternating current (AC) interference corrosion is one of the main causes of corrosion failure of X80 pipeline steel (Zhu et al, 2014a;Fu and Cheng, 2012;Kuang and Cheng, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Zhu et al (2014a) showed that AC interference exceeding 100░ A/m 2 in a high pH environment may generate hydrogen atoms and cause HIC, increasing the stress corrosion cracking sensitivity of X80 steel. Research by Fu and Cheng (2012) and Kuang and Cheng (2017) showed that AC interference affected the stability of X80 steel's cathodic protection potential, resulting in excessive cathodic protection and hydrogen evolution reaction. Research by Wan et al (2017a) showed that the negative half-wave current (NC) promoted the hydrogen evolution reaction of X80 steel and increased the stress corrosion cracking sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Alternating current (AC) corrosion refers to the corrosion process that may occur under the action of AC stray current or AC induced voltage on pipeline steel even though the cathodic protection system existed. Typically, AC corrosion is the electrochemical corrosion reaction to promote pipeline failure (Hu et al, 2010;Fu and Cheng, 2010;Fu and Cheng, 2012;Kuang and Cheng, 2017). Because of burying crosswise or parallelly with high voltage transmission line and AC electrified railways, AC stray current will produce in the pipeline and outflow the pipeline through the coating defect, causing AC corrosion perforation (Mi, 2008).…”
Section: Introductionmentioning
confidence: 99%